Democracy and New Media: Capturing Masculinity in Online News About Election Selfie - Monika Sri Yuliarti (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2020)
Election selfie has been a quite phenomenon since the 2014 election in Indonesia. In the last election, 2019, there was a famous actor, Nicholas Saputra, who posted his inked finger selfie in his Instagram account as one of his campaign efforts for the youth to be involved in the election, and surprisingly, it became a bombshell in the online world. This study examined the representation of masculinity in the online new relates to the election selfie by Nicholas Saputra. This research involved five (5) online news articles from a reputable online news portal in Indonesia using a critical discourse analysis perspective that was adopted from the Sara Mills model. It was found that traditional masculinity was represented in research objects, which were the strengths and the practical way of life. Moreover, it was also found that in terms of subject-object position, there was no balance in the opportunity to speak between the subject and object. Finally, as to the writer-reader position, the writer also held a more significant privilege to decide the position of the reader.